Understanding fragility fracture patients' decision-making process regarding bisphosphonate treatment. Issue 1 (January 2017) - Wozniak, L.; Johnson, J.; McAlister, F.; Beaupre, L.; Bellerose, D.; Rowe, B.; Majumdar, S.
Abstract Summary We aimed to understand how patients 50 years and older decided to persist with or stop osteoporosis (OP) treatment. Processes related to persisting with or stopping OP treatments are complex and dynamic. The severity and risks and harms related to untreated clinical OP and the favorable benefit-to-risk profile for OP treatments should be reinforced. Introduction Older adults with fragility fracture and clinical OP are at high risk of recurrent fracture, and treatment reduces this risk by 50 %. However, only 20 % of fracture patients are treated for OP and half stop treatment within 1 year. We aimed to understand how older patients with new fractures decided to persist with or stop OP treatment over 1 year. Methods We conducted a grounded theory study of patients 50 years and older with upper extremity fracture who started bisphosphonates and then reported persisting with or stopping treatment at 1 year. We used theoretical sampling to identify patients who could inform emerging concepts until data saturation was achieved and analyzed these data using constant comparison. Results We conducted 21 interviews with 12 patients. Three major themes emerged. First, patients perceived OP was not a serious health condition and considered its impact negligible. Second, persisters and stoppers differed in weighting the risks vs benefits of treatments, where persisters perceived less risk and more benefit. Persisters considered treatment "required" while stoppers often deemed treatment "optional." Third, patients could change treatment status even 1-year post-fracture because they re-evaluated severity and impact of OP vs risks and benefits of treatments over time. Conclusions The processes and reasoning related to persisting with or stopping OP treatments post-fracture are complex and dynamic. Our findings suggest two areas of leverage for healthcare providers to reinforce to improve persistence: (1) the severity and risks and harms related to untreated clinical OP and (2) the favorable benefit-to-risk profile for OP treatments.